KALIMANTAN TIMUR : DAERAH KAYA VERSI SIAPA? - Erny Murniasih (Jurnal Borneo Administrator, 2008)
The simplest way to understand decentralisation is bringing the government closer to its people. From the economic view, the implementation of decentralisation will improve  in economic efficiency, service delivery, and accountability. In Indonesia, decentralisation has developed in form of political, fiscal, and administrative decentralisation. In fiscal decentralisation, the country applies the money follows function principle as a means to give fiscal balance between central and sub-national governments. Therefore,SNG’s are granted with local-own sources and intergovernmental fiscal transfers to finance the assigned functions. The main objective for fiscal decentralisation is to increase welfare at the local level. To what extent that this occur in Province East Kalimantan? The fact that the Province has a substantial revenue from natural resources which makes its GRDP increased. Theoretically, an increase in GRDP will affect on the increase number of employment and on the reduction of the poor. However, what has happened in East Kalimantan is on the reverse side. Increase in GRDP does not necessarily reveal that the people, particularly the poor, would be better-off. This paper tries to analyse the case and provides with possible solution.  Keywords : Desentralisasi Fiskal, Dana Perimbangan, Dana Bagi Hasil Sumber Daya Alam